(untitled) (Materiali di Estetica. Terza serie, 2022)
Salvatore Veca (31 October 1943 - 7 October 2021) was not only a lecturer in many universities, including eventually Pavia, but also an active intellectual in many important civic structures. A brilliant pupil of Enzo Paci at the University of Milan, editor of the journal «aut aut», Veca chaired the Fondazione Feltrinelli and the Casa della Cultura in Milan and was the author of many books on philosophy based on the critical introduction of Anglo-Saxon analytical culture. The presentation in Italy of the work of John Rawls was important and marked the liveliest interest in the problem of the “just society”. He played a leading role in the debate on the possible developments of the Italian left after the fall of the Berlin Wall. For the Expo Laboratory he was responsible for drafting the “Milan Charter” on environmental sustainability.